EVALUATING THE PHYSICAL ENVIRONMENT AT SUMOBOO RESTAURANT AND DESSERT HOUSE BY USING IMPORTANCE AND PERFORMANCE ANALYSIS (IPA) - Pangkey, Giacita C. M.; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The role of the physical environment in influencing customer behaviors and in creating a provider’s image is especially pertinent in a service industry such as the restaurant industry. What appeals to consumer preferences is not just food and drink, but also a pleasant dining environment. Increased attention is paid not only to the price and the merchandise itself, but also to providing a pleasant and possibly exciting shopping atmosphere. This research aims to identify how the Physical Environment at Sumoboo Restaurant and Dessert House. Type of this research is descriptive with quantitative approach and IPA used as the measurement tool. The sample size will be 100 customers. The result for service quality shows, There are two attributes that perceived important to the customer which are Cleanliness and Equipment. Those attributes was performed well by Sumoboo then placed in Quadrant 2. In Quadrant 1, the attributes are Scent. In Quadrant 3, the attributes are Temperature, Music, and Symbol. In Quadrant 4, the attributes are Lighting, Colors, Layout, Furnishing and Decoration. From the result the researcher suggests that Sumoboo Restaurant and Dessert House must have to keep up with the performance that they already given and continuously developing each day. Keywords: importance and performance Analysis, physical environment.